Personality and demographic correlates of political ideology. (February 2022) - Furnham, Adrian; Horne, George
Abstract: This paper was concerned with "bright" and "dark-side" personality trait correlates of political beliefs. In a series of three studies we asked people to rate their political beliefs on a simple, single, left-right, liberalism-conservatism dimension. We used three British Prolific samples: N = 500 (study 1); N = 506 (study 2) and 223 (study 3). Our major focus was on how much incremental variance can be accounted for by trait variables over demographic and other belief variables. In the first study we found three personality traits, particularly Conscientiousness was related to right-wing/Conservative and Openness to left-wing Liberal political beliefs: personality accounted for around 8% incremental variance over demographic and other belief variables. In the second study we found fewer significant correlations between personality and political beliefs, accounting for 3% of the variance but that the Militant Extremist Mindset factors added another 2% of the variance. In the third study we found evidence that three "dark-side" personality disorder factors namely Narcissism, Psychopathy and Sadism accounted for around 5% of incremental variance over demographic and belief variables. The implications and limitations of the results are discussed. Highlights: Three studies looked at "bright" and "dark-side" personality trait correlates of political beliefs. Study 1 showed three traits related to political beliefs Study 2 found Militant Extremist Mindset factors were related to political beliefs. Study 3 found Narcissism, Psychopathy and Sadism accounted for 5% of incremental variance.